Handbook on the geographies of corruption - Warf, Barney (Research handbooks in geography, 2018)
The Handbook on the Geographies of Corruption is a comprehensive overview of corruption, exploring the immense variation of corruption among nations, and how this reflects levels of wealth, the centralization of power, colonial legacies, and different national cultures